Husserl's Phenomenological Perspective In Facing Changes In The New Normal Era Of Education Development Of COVID-19 Pandemic - Artika Artika; Nofri Yuhelman; Jimmi Copriady; Bustanur Bustanur (Entalpi Pendidikan Kimia, 2022)
Abstract Writing this article aims to discuss Husserl's Phenomenological Perspective in Facing Changes in Educational Development in the New Normal Era of the Covid-19 Pandemic. Phenomenology conceives of what you see in your consciousness, or what you see only as much as you can see. The method used in writing this article is a qualitative descriptive method. Supporting sources in writing this article are taken from scientific books and scientific journals. The data collection technique in this study is a literature study. In a phenomenological perspective, the characteristics of phenomenology are presented to study self-awareness in the face of the covid-19 pandemic, the phenomenological process in forming awareness to be creative in learning the new normal. Keywords: Phenomenology, Education, New Normal, Covid-19 Pandemic